Correlating disordered activation domain ensembles with gene expression levels - Eduardo Flores; Aleah R. Camacho; Estefania Cuevas-Zepeda; Mary B. McCoy; Feng Yu; Max V. Staller; Shahar Sukenik (Biophysical Reports)
Transcription factor proteins bind to specific DNA promoter sequences and initiate gene transcription. These proteins often contain intrinsically disordered activation domains (ADs) that regulate their transcriptional activity. Like other disordered protein regions, ADs do not have a fixed three-dimensional structure and instead exist in an ensemble of conformations. Disordered ensembles contain sequence-encoded structural preferences that are often linked to their function. We hypothesize that this link exists between the structural preferences of AD ensembles and their ability to induce gene expression. To test this, we measured the ensemble dimensions of two ADs, HIF-1α and CITED2, in live cells using fluorescence resonance energy transfer microscopy and correlated this structural information with their transcriptional activity. We find that mutations that expanded the ensemble of HIF-1α increased transcriptional activity, while compacting mutations reduced it, highlighting the critical role of structural plasticity in regulating HIF-1α function. Conversely, CITED2 showed no correlation between ensemble dimensions and activity. Our results highlight a possible link between AD ensemble dimensions and their transcriptional activity, with implications for transcriptional regulation and dysfunction.